After Stalingrad : the Red Army's winter offensive, 1942-43 - Glantz, David M. (Helion & Co., 2011)
In the wake of the Red Army's signal victory at Stalingrad, which began when its surprise counteroffensive encircled German Sixth Army in Stalingrad region in mid-November 1942 and ended when its forces liquidated beleaguered Sixth Army in early February 1943, the Soviet High Command (Stavka) expanded its counteroffensive into a full-fledged winter offensive which nearly collapsed German defenses in southern Russia. History has recorded the many dramatic triumphs the Red Army achieved during the initial phases of this winter offensive, culminating with its rapid advance deep into the Donbas an.